OLD BATTLES AND NEW FUNERARY MONUMENTS: TOMBSTONES ALONG SACRED ROUTES IN CLASSICAL ATTICA. - Sears, Matthew A. (Hesperia)
Taking the well-known "Marathon Stone" as a starting point, this article proposes that certain late 5th- and 4th-century bce Attic funerary monuments were situated in such a way as to advertise a connection to a famous battlefield, even if the deceased had no personal connection to the relevant battle. Several monuments discovered outside of the deme named in their inscription stood on or near the plain of Marathon, along the renowned route between Marathon and Athens, or on the island of Salamis, while other monuments were set along sacred ways to sanctuaries such as those at Eleusis, Brauron, and Cape Zoster; this suggests a possible parallel between the routes to battlefields and sacred ways to sanctuaries. Accordingly, this article suggests a new avenue for the study of Attic funerary practices: namely, it elucidates a possible way in which the burial of the dead related to Athens's military past and the sacred landscape.